Enhancing organophosphate hydrolase efficacy via protein engineering and immobilization strategies. Issue 1 (19th August 2020) - Katyal, Priya; Chu, Stanley; Montclare, Jin Kim
Abstract: Organophosphorus compounds (OPs), developed as pesticides and chemical warfare agents, are extremely toxic chemicals that pose a public health risk. Of the different detoxification strategies, organophosphate‐hydrolyzing enzymes have attracted much attention, providing a potential route for detoxifying those exposed to OPs. Phosphotriesterase (PTE), also known as organophosphate hydrolase (OPH), is one such enzyme that has been extensively studied as a catalytic bioscavenger. In this review, we will discuss the protein engineering of PTE aimed toward improving the activity and stability of the enzyme. In order to make enzyme utilization in OP detoxification more favorable, enzyme immobilization provides an effective means to increase enzyme activity and stability. Here, we present several such strategies that enhance the storage and operational stability of PTE/OPH. Abstract : Organophosphorus compounds (OPs) are extremely toxic chemicals that pose a public health risk. Organophosphate‐hydrolyzing enzymes are a potential route for detoxifying those exposed to OPs, and phosphotriesterase (PTE) is one such enzyme. In this review, we will discuss the protein engineering of PTE aimed towards improving the activity and stability of the enzyme. We also present several enzyme immobilization strategies that enhance the storage and operational stability of PTE.